Separate and joint effects of alcohol and smoking on the risks of cirrhosis and gallbladder disease in middle-aged women. - Liu, B; Balkwill, A; Roddam, A; Brown, A; Beral, V (2009)
The separate and joint effects of alcohol and smoking on incidences of liver cirrhosis and gallbladder disease were examined in a prospective study of 1,290,413 United Kingdom women (mean age, 56 years) recruited during 1996-2001. After a mean follow-up of 6.1 years (1996-2005), incidence rates of cirrhosis and gallbladder disease were 1.3 per 1,000 persons (n = 2,105) and 15 per 1,000 persons (n = 23,989), respectively, over 5 years. Cirrhosis risk increased with increasing alcohol consumption, while the risk of gallbladder disease decreased (P(trend) < 0.0001 for each). Comparing women who drank > or =15 units/week with those who drank 1-2 units/week, the relative risk was 4.32 (95% confidence interval (CI): 3.71, 5.03)) for cirrhosis and 0.59 (95% CI: 0.55, 0.64) for gallbladder disease. Increasing numbers of cigarettes smoked daily increased the risk of both conditions (P(trend) < 0.0001 for each). Comparing current smokers of > or =20 cigarettes/day with never smokers, the relative risk was 3.76 (95% CI: 3.25, 4.34) for cirrhosis and 1.29 (95% CI: 1.22, 1.37) for gallbladder disease. Effects of alcohol and smoking were more than multiplicative for cirrhosis (P(interaction) = 0.02) but not for gallbladder disease (P(interaction) = 0.4). Findings indicate that alcohol and smoking affect the risks of the 2 conditions in different ways. For cirrhosis, alcohol and smoking separately increase risk, and their joint effects are particularly hazardous. For gallbladder disease, alcohol reduces risk and smoking results in a small risk increase.